Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Ika Neni Kristanti (Institut Bisnis dan Informatika Kesatuan, 2022)
The purpose of this research was to determine the effect of corporate social responsibility on firm value with profitability as a moderating variable for manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2020 periods. The population used in this study are various industrial sub-sector manufacturing companies that have gone public that disclose CSR and are listed on the Indonesia Stock Exchange in 2019-2022, totaling 22 companies. The sampling technique used was the documentation purposive sampling method. The data used is secondary data and uses a data collection method, namely a documentation study by collecting secondary data published by the IDX. The analytical technique used is multiple data regression analysis with the help of SPSS 25 software application. The results show that: 1) Corporate Social Responsibility has a significant effect on firm value; 2) Profitability is able to moderate the effect of Corporate Social Responsibility on firm value.